Development of Donepezil Hydrochloride Loaded Gellan Gum Based Nasal Mucoadhesive Microspheres by Spray Drying Method - Gangane, Purushottam; Kawtikwar, Pravin (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: The aim of present study was the formulation of donepezil hydrochloride loaded polymeric mucoadhesive microspheres for delivery via nasal route to increase the residence time and absorption of drug from the nasal mucosa. Methodologies: The microspheres were formulated by conventional spray drying technique by using gellan gum as a mucoadhesive polymer. A 32 full factorial design was utilized with polymer concentration (X1) and liquid feed flow rate (X2) as independent variables in formulation of the microspheres and their effect was studied on entrapment efficiency, particle size and drug loading. Results: The results specified that the X1-X2 interaction had significant effect on drug loading while X2 alone effect on entrapment efficiency and particle size. The optimized microspheres were further evaluated for drug release kinetic study, histological examination, ex vivo permeation study and stability study. Conclusion: It was concluded that the gellan gum containing microspheres of donepezil hydrochloride with mucoadhesive property are suitable for nasal delivery.
Keywords: Mucoadhesion; Intranasal; Microsphere; Donepezil hydrochloride; Spray; drying